Estrogen Promotes Pro-resolving Microglial Behavior and Phagocytic Cell Clearance Through the Actions of Annexin A1 - Loiola, Rodrigo Azevedo; Wickstead, Edward S.; Solito, Egle; McArthur, Simon (Frontiers in Endocrinology, 2019)
Estrogen promotes pro-resolving microglial behaviour and phagocytic cell clearance through the actions of annexin A1